1987
DOI: 10.3168/jds.s0022-0302(87)80299-0
|View full text |Cite
|
Sign up to set email alerts
|

Intercorrelations Among Milk Production Traits and Body and Udder Measurements in Holstein Heifers

Abstract: Data from 1341 Holstein heifers of 71 sires were used to study heritabilities of and genetic and phenotypic correlations among milk production traits (308-d milk, front and rear half yields), body measurements (heart girth, withers height, body length, and rump length), udder measurements (front teat length and diameter, rear teat length and diameter, teat distance and udder height), and age at first calving. Genetic and phenotypic parameters were estimated by the multitrait restricted maximum likelihood metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 17 publications
5
20
0
Order By: Relevance
“…They found that milk production traits (308-d milk, front and rear half yields) were positively correlated with body measurements (heart girth, wither height, body length, and rump length). The results of the present study, which found height at withers and rump length, positively and significantly related to profit measures DLP, ADLP LTL , ADLP LPL , and EF agree with those of Lin et al (1987). These traits were, however, not significantly related to DLPOC (Table 9).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…They found that milk production traits (308-d milk, front and rear half yields) were positively correlated with body measurements (heart girth, wither height, body length, and rump length). The results of the present study, which found height at withers and rump length, positively and significantly related to profit measures DLP, ADLP LTL , ADLP LPL , and EF agree with those of Lin et al (1987). These traits were, however, not significantly related to DLPOC (Table 9).…”
Section: Discussionsupporting
confidence: 72%
“…These positive correlations suggest that cows that have high milk production in first lactation were taller and larger than low producers. Lin et al (1987) also found negative phenotypic correlations between udder height and yield traits, implying that high producing heifers tend to have lower udders. The current study found corresponding results (Table 9).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In dairy cows, milk production is positively correlated with size (Lin et al, 1987) which has contributed to selection for larger animals even though these are not necessarily the most efficient. Several studies have investigated associations between SNP in the leptin system with growth, milk production and fertility traits.…”
Section: Genetic Selectionmentioning
confidence: 99%